2014
DOI: 10.1002/jhet.2080
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Heterocyclic and Polycyclic Compounds from Amino Alcohols and Dialdehydes

Abstract: Amino alcohols typically react with aldehydes to produce oxazolidines. It was hypothesized that the condensation of several commercially available amino alcohols with dialdehydes would produce a series of bicyclic oxazolidines containing two secondary amines. However, there were remarkable differences in the type of products formed depending on the structure of the dicarbonyl compounds and the reaction conditions. When linear aliphatic dialdehydes such as glyoxal were used, the expected bis‐oxazolidines were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Fu and Chen reported the synthesis of diaminoalcohols via stereoselective Ugi-reaction starting from α,α'-iminodiacetic acid analogues 109. Reaction of nitroalkanes with α,β-unsaturated aldehydes and subsequent catalytic hydrogenation can also lead to the aforementioned moiety 110. Rondotet al reported the efficient regio-and stereoselective synthesis of diaminoalcohol derived dihydrooxazines (CXIX) from readily accessible aminodiol CXVIII via trichloroacetimidate intermediates.…”
mentioning
confidence: 99%
“…Fu and Chen reported the synthesis of diaminoalcohols via stereoselective Ugi-reaction starting from α,α'-iminodiacetic acid analogues 109. Reaction of nitroalkanes with α,β-unsaturated aldehydes and subsequent catalytic hydrogenation can also lead to the aforementioned moiety 110. Rondotet al reported the efficient regio-and stereoselective synthesis of diaminoalcohol derived dihydrooxazines (CXIX) from readily accessible aminodiol CXVIII via trichloroacetimidate intermediates.…”
mentioning
confidence: 99%